2021
DOI: 10.46827/ejes.v8i12.4060
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ Attitudes Towards Portfolio Assessment: A Study on Elt and Ell Students

Abstract: <p>The current study set out to define ELT and ELL students' attitude towards portfolio assessment in academic writing and to define the positive and negative aspects of portfolio assessment along with the aims to define their preferences on choosing portfolios versus traditional pen-and-paper tests. The sample of this study consists of 49 students studying English Language Teaching (ELT) and English Language and Literature departments at Tokat Gaziosmanpaşa University in the second term of academic year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This assessment practice offers numerous benefits for both educators and students, as aligned with the findings of the study. For students, portfolio assessment promotes deeper engagement with course materials, encourages reflection, and fosters a sense of ownership over their learning journey [16,17,37]. Additionally, portfolio assessment provides opportunities for students to demonstrate their understanding of concepts in diverse ways, catering to different learning styles and preferences [3,9,13].…”
Section: Implications For Portfolio Assessment Practicesmentioning
confidence: 99%
See 4 more Smart Citations
“…This assessment practice offers numerous benefits for both educators and students, as aligned with the findings of the study. For students, portfolio assessment promotes deeper engagement with course materials, encourages reflection, and fosters a sense of ownership over their learning journey [16,17,37]. Additionally, portfolio assessment provides opportunities for students to demonstrate their understanding of concepts in diverse ways, catering to different learning styles and preferences [3,9,13].…”
Section: Implications For Portfolio Assessment Practicesmentioning
confidence: 99%
“…Studies have highlighted the positive impact of portfolio assessment on student learning outcomes, such as improved critical thinking skills, self-regulation, and motivation [6,13,14]. Furthermore, it has been shown that portfolio assessment promotes deeper understanding [15], fosters student engagement and ownership of learning [3,16], and provides opportunities for authentic assessment and reflection [4,10]. Moreover, Kharbach [4], Ghoorchaei &Tavakoli [7], and Sewell et al [12], highlight that the formative nature of portfolio assessment allows it to be used as a powerful tool for guiding instructional decision-making and fostering student growth through tracking and evaluating their progress over time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations